How an Economy Grows and Why It Crashes. - Schiff, Peter D. (Wiley, 2013)
Straight answers to every question you've ever had about how the economy works and how it affects your life In this Collector's Edition of their celebrated How an Economy Grows and Why It Crashes, Peter Schiff, economic expert and bestselling author of Crash Proof and The Real Crash, once again teams up with his brother Andrew to spin a lively economic fable that untangles many of the fallacies preventing people from really understanding what drives an economy. The 2010 original has been described as a "Flintstones" take economics that entertainingly.